On Asymptotics for Critical Solutions of Systems of Differential Equations with Oscillatory Decreasing Coefficients - P. N. Nesterov (Моделирование и анализ информационных систем)
In this paper we propose a method for constructing the asymptotics for a set of linear independent solutions of systems of differential equations with oscillatory decreasing coefficients. We illustrate this method by constructing the asymptotics for solutions of a system of two oscillators with slowly decreasing coupling and friction in one of the oscillators.